Budaya Sekolah Berbasis Keislaman sebagai Sarana Penguatan Nilai Pancasila : (Studi pada Kegiatan Ramadhan di SMA Islam Al Ulum Terpadu Medan) - Rizka Arni Sagala; Nayla Firzanah; Murni Murni; Hasnah Masroida Hasibuan; Prita Nurjanah; Diva Dea Amanda (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
Education plays a crucial role in shaping students' character based on Pancasila values. However, in the era of globalization, these values are increasingly eroded by external cultural influences. To address this, Islamic-based schools integrate Pancasila values into school culture through various religious activities. This study aims to analyze how the Islamic-based school culture at SMA Islam Al Ulum Terpadu Medan contributes to strengthening Pancasila values. This research employs a descriptive qualitative method with a quantitative approach. Data were collected through observations, interviews with teachers and student organization leaders (Rohis), and questionnaires distributed to 40 students from grades X, XI, and XII. The findings indicate that various programs, such as Tadarus before lessons, Hafalan Tahfiz, Tarbiyah Ramadhan, and Pesantren Kilat, help instill discipline, teamwork, and social awareness among students. Approximately 75% of students reported that these activities enhanced their understanding and practice of Pancasila values in daily life. However, the study also identified several challenges, including a lack of variation in teaching methods and the need for innovation to make activities more engaging for students. Therefore, developing more interactive and innovative methods is necessary to improve the effectiveness of these programs in shaping students' character based on Pancasila.